Developing a Jimdo-Based Ekanaru Learning Platform Using Problem-Based Learning to Support Elementary Students’ Explanatory Writing Skills - Widyarini Susilo Putri; Widyarini Susilo Putri; Riska Awalulhikmah; Heny Kusuma Widyaningrum; Nur Samsiyah; Riska Awalulhikmah; Heny Kusuma Widyaningrum; Nur Samsiyah (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
This study aims to describe the development process and assess the suitability of the Ekanaru learning resource, based on the Jimdo website and using the Problem-Based Learning (PBL) model, for teaching writing skills to fifth-grade public elementary school in Indonesia. The study employed the Research and Development (R&D) method using the ADDIE model, which comprises the stages of analysis, design, development, implementation, and evaluation. The research subjects comprised 13 Year 5 students. Product validation involved one media expert, one subject, and a language expert. Data were collected through observation, interviews, questionnaires, and documentation, and subsequently analyzed using quantitative descriptive techniques, expressed as percentages. The learning resource developed was integrated with the Problem-Based Learning (PBL) model on the Jimdo website platform. The validation results showed an average feasibility percentage of 84.14%, categorized as ‘highly suitable’. Teacher feedback scored 90%, and students' feedback 88.46 %, both falling into the ‘very good’ category. The evaluation results showed that students were able to compose explanatory texts in the correct structure and achieved good learning outcomes. The Ekanaru learning media, based on the Jimdo website and using the PBL model, is suitable for supporting the development of explanatory text writing skills among fifth-grade elementary school students.